PENGARUH TEMPAT DAN PROMOSI TERHADAP PEMBELIAN PADA UKHUWAHMART BANJARMASIN - Rahmat Hilmi; Anthonius J. Karsudjon (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2019)
The purpose of this study was to determine the effect of the independent variable place and promotion both simultaneously and partially on the dependent variable of purchasing decisions on the Ukhuwah Mart Banjarmasin. And want to know the dominant variables that influence purchasing decisions on the Ukhuwah Mart Banjarmasin. The data used is the result of distributing questionnaires to respondents who shop at the purchase decision on the Ukhuwah Mart Banjarmasin. The sample selection technique is Accindental Sampling with a total of 89 consumers. Data processing techniques using SPSS (Statistical Package for the Social Sciences). The results showed that the overall place and promotion variables simultaneously influence the purchasing decision variables on the Ukhuwah Mart Banjarmasin of 35,161. The influence of place and promotion variables partially on purchasing decisions on Ukhuwah Mart Banjarmasin, namely 5,947/0.000 place and 2,962/0.004 promotion. Promotional variables have a dominant influence on purchasing decisions at Ukhuwah Mart Banjarmasin. This means that according to consumers' perception of promotion factors become something that is considered important in efforts to create purchasing decisions on the Ukhuwah Mart. Referring to the terminated Coefficient (R Square) of 0.450, the purchase decision on the Ukhuwah Mart 45% is influenced by place and promotion variables. While the remaining 55% of purchasing decisions are influenced by other variables not included in this study.